Pengaruh Rasio Pertumbuhan, Rasio Efektivitas, dan Rasio Efisiensi terhadap Kesejahteraan Masyarakat di Daerah Istimewa Yogyakarta (DIY) - Enggar Cahyaning; Fuadhillah Putri (Yayasan Literasi Ilmiah Indonesia, 2022)
Purpose: This study aims to test the influence of growth ratio, effectivity ratio, and efficiency ratio on social welfare in Daerah Istimewa Yogyakarta (DIY). Method: The method used in this study is purposive sampling with the availability of Report on local government finances (LKPD) and audit opinion as the criteria. The sample used is 6 LKPD in DIY each year or 78 total of objects. The data is proceeded by using EVIEWS. Finding: The first hypothesis is that the growth ratio has a significant positive effect on social welfare. The second hypothesis is that the ratio of effectiveness has a significant positive effect on social welfare. The third hypothesis is that the efficiency ratio has a significant positive effect on social welfare. The last hypothesis is that growth ratios, effectiveness ratios, and efficiency ratios have a significant positive effect on social welfare collectively. Novelty: DIY, one of the tourism cities in Indonesia with a low cost of living, is interesting to test the social welfare by using growth ratio, effectiveness ratio, and efficiency ratio. Keywords: growth ratio, effectiveness ratio, efficiency ratio, social welfare